2013
DOI: 10.1021/ct4005849
|View full text |Cite|
|
Sign up to set email alerts
|

Harmonic Models in Cartesian and Internal Coordinates to Simulate the Absorption Spectra of Carotenoids at Finite Temperatures

Abstract: When large structural displacements take place between the ground state (GS) and excited state (ES) minima of polyatomic molecules, the choice of a proper set of coordinates can be crucial for a reliable simulation of the vibrationally resolved absorption spectrum. In this work, we study two carotenoids that undergo structural displacements from GS to ES minima of different magnitude, from small displacements for violaxanthin to rather large ones for β-carotene isomers. Their finite-temperature (77 and 300 K) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(128 citation statements)
references
References 69 publications
3
120
1
Order By: Relevance
“…This has been debated in recent years between Cartesian and internal coordinate systems. 52,53 While it has been shown that internal coordinate system yield better results for the vibronic equations due to the fact that there are less coordinates displaced versus the Cartesian system, some of the same researchers have produced significant work and comparisons in Cartesian coordinates. 54,55 In addition to comparisons between the adiabatic and vertical Hessian.…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…This has been debated in recent years between Cartesian and internal coordinate systems. 52,53 While it has been shown that internal coordinate system yield better results for the vibronic equations due to the fact that there are less coordinates displaced versus the Cartesian system, some of the same researchers have produced significant work and comparisons in Cartesian coordinates. 54,55 In addition to comparisons between the adiabatic and vertical Hessian.…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…This is particularly true for the AH model, since the necessity to project S 0 and S 1 normal modes computed at very different geometries, yields huge broadenings caused by exaggerated Duschinsky mixings, an artifact connected to the inadequacy of normal coordinates to describe large distortions of the molecular structure. Several groups are currently working to extend the capability of available models toward large and flexible compounds, adopting for instance a description of normal modes in internal coordinates and/or separating few large‐amplitude anharmonic motions to be treated at quantum or classical levels of theory . Different schemes for introducing anharmonic corrections on the frequencies and vibrational wavefunctions have been proposed considering either a perturbation expansion of the anharmonic potential, or exploiting prescreening techniques similar to those adopted in TI harmonic approaches .…”
Section: Illustrationsmentioning
confidence: 99%
“…In the context of global harmonic methods, there are two natural possibilities of constructing a final-state harmonic potential using the initial-state Hessian: one can either compute the potential energy and gradient of the final-state potential energy surface at the initial geometry, which results in the vertical gradient model, or optimize the geometry in the final electronic state, which gives the adiabatic shift model. 13,50,52 Both the vertical gradient and adiabatic shift models are examples of displaced harmonic systems, and thus ignore mode distortion and mixing (the Duschinsky effect) between the two electronic states. In the results section, we discuss only the adiabatic shift model and, for consistency with the other methods discussed in this work, refer to it as the initial harmonic model.…”
Section: F Reference Hessiansmentioning
confidence: 99%